An Efficient Synthesis of N-Cyclopropylanilines by a Smiles Rearrangement - Arava, Veera Reddy; Bandatmakuru, Sreenivasula Reddy (Synthesis, 2013)
Treatment of 2-chloro-N-cyclopropylacetamide with phenols gave the corresponding 2-aryloxy-N-cyclopropylacetamides, which on treatment with a base gave the corresponding N-cyclopropylanilines.
Keywords: rearrangements; amines; cyclopropanes